2014
DOI: 10.1111/jch.12418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Masked Hypertension in African Americans

Abstract: Masked hypertension (MH), the presence of normal office blood pressure (BP) with elevated ambulatory pressure, has been shown to correlate with organ damage. Population‐based studies from Europe and Asia estimate a prevalence of 8.5% to 15.8%. Two small studies in African Americans estimate a prevalence >40%. Therefore, the authors utilized ambulatory BP monitoring (ABPM) to identify the prevalence of MH in our African American population. Pressure was recorded every 30 minutes while awake and every 60 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…A similar prevalence of MHT (45%) has been reported in African Americans, and in African Americans with hypertensive kidney disease (43%) . Among this renal‐impaired MHT group, more cases showed uncontrolled nighttime ABPM (94%) than uncontrolled daytime ABPM (57%).…”
Section: Discussionsupporting
confidence: 73%
“…A similar prevalence of MHT (45%) has been reported in African Americans, and in African Americans with hypertensive kidney disease (43%) . Among this renal‐impaired MHT group, more cases showed uncontrolled nighttime ABPM (94%) than uncontrolled daytime ABPM (57%).…”
Section: Discussionsupporting
confidence: 73%
“…Two small studies (each <100 participants), which included middle-aged AAs, have reported a prevalence of masked hypertension exceeding 40%. 32, 33 Also, in the African American Study of Kidney Disease (AASK) Cohort Study, which included 691 AAs with established kidney disease, 70% of participants had masked daytime or nighttime hypertension. 30 In the current study, approximately 30% of AAs had masked daytime and 24-hour hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We used data from a population-based sample comprised entirely of AAs. There have been few prior investigations of ABPM among AAs, 4,46 and this population has a high risk for masked hypertension 4 and incident clinic hypertension. 12 Also, given the broad data collection in the JHS, we were able to control for multiple potential confounders.…”
Section: Discussionmentioning
confidence: 99%